A study on the application of promotional mix towards cottage industry products at Risda Negeri Melaka / Farhana Mohd Salim - Mohd Salim, Farhana (Faculty of Business and Management, 2010)
Agriculture in this country is experiencing significant transformation towards a more dynamic and competitive sector. This sector is critical in the sense that it is not only contributed to economic growth but also can contribute to creating job opportunities. The development of agro-based small and medium industries (SMI) is emphasized in the nation’s Agriculture Policy because it is expected to enhance the value-added of the agro-products. Even though the move by the government to make Malaysia as a global hub for food producing and chain by 2010, the achievement of SMI Bumiputera agropreneurs is still at low level. Cottage industries are one of the SMI businesses. This case study utilized quantitative and qualitative approaches. Based on the objective and literature review a set of interview protocol and site visit was developed in order to collect pertinent data for this study. A sample of eight smallhoders in the sated of Melaka that registered under RISDA Negeri Melaka was selected. The study found that, smallholders acknowledged that their marketing and promotional strategy were weak. Further, the results of the site visit and document analysis shows that, in general, the smallholder’s management of finance was poor and low return on investment.